Positioning of infants in the neonatal intensive care unit for lumbar puncture as determined by bedside ultrasonography. Issue 2 (9th June 2012) - Öncel, Selim; Günlemez, Ayla; Anık, Yonca; Alvur, Müge
Abstract : Realising the paucity of data in the standardisation of the optimal position for lumbar puncture (LP) in hospitalised neonates, we have designed an observational study to measure the interspinous distance in infants in a university hospital setting. The infants were placed in two lateral recumbent and two upright positions (lateral recumbent without flexing the hips, lateral recumbent with maximal hip flexion, sitting without flexing the hips and sitting with maximal hip flexion) with concomitant heart rate (HR), transcutaneous oxygen saturation (OS) and interspinous distance (with ultrasonography) measurements. Having the patient sit with maximal hip flexion provided the largest interspinous space for the grand majority of the infants. Sitting positions with/without flexion have resulted in significant increases in HR with respect to lateral recumbent position without flexion. Although statistically significant drops in OSs have been observed between lateral recumbent and sittting with flexion, lateral recumbent with flexion and sitting without flexion, and lateral recumbent with flexion and sitting with flexion positions; no adverse hypoxic events occurred during positioning. Sitting flexed position, which seems to be sufficiently safe and serve to enhance the success rate of a LP, should be favoured for sick neonates whenever the infant's condition permit a spinal tap.